Handbook on opium : history and basis of opioids in therapeutics - Kumar, Vasanth (Academic Press, 2022)
"Handbook of Opium: History and Basis of Opioids in Therapeutics traces the history of poppy from its prehistory, its use in Greek and Egyptian medicine through the European Renaissance, and the opioid epidemic of the present day. The book explores the discovery of morphine and its alkaloids, reviews its biosynthetic process, and covers the evolution of synthetic opioids. Further, it reviews the biological effects of opium and the molecular basis of its actions, including future perspectives in clinical applications with therapeutic targets. The book is interspersed with numerous notes on the events and great minds in history and medicine who advocated, analyzed and advanced opium through history. The book is a comprehensive review on opium, covering a breadth of topics, including its history, botany, chemistry, trade, physiology, clinical use and molecular biology, with numerous references, tables, vignettes and illustrations included for additional understanding."--Publisher.